The Mystery of the Spirit in Three Traditions: Calvin, Rahner, Florensky Or, You Keep Wondering Where the Spirit Went - Rogers, Eugene F., Jr. ca. 20./21. Jh. (Modern theology, 2003)
Nineteenth- and twentieth-century North Atlantic theology has seen a succession of Trinitarian revivals. Some observers take as an index of a theologian's success whether he or she has much interesting to say about the Holy Spirit, and some, including Robert Jenson, have also noted a tendency to announce the Spirit and talk about the Son. While Rogers shares that concern, he qualifies the characterization to note that authors in three traditions sometimes admit the charge and demur, claiming that is how it should be, citing passages in Calvin, Rahner, and Pavel Florensky. Of these the boldest is Florensky, who anticipates Jenson's critique but, writing in 1913, makes it not of Barth but of Eastern Orthodox theology (usually seen as a model to follow here), even in its liturgy. Rogers leaves this puzzle unresolved.